The Oxford handbook of the economics of gambling - Siegel, Donald S., 1959-; Vaughan Williams, Leighton (New York : Oxford University Press, 2013)
This handbook is a definitive source of path-breaking research on the economics of gambling. It is divided into sections on casinos, sports betting, horserace betting, betting strategy motivation, behaviour and decision-making in betting markets prediction markets and political betting, and lotteries and gambling machines.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 15, 2013).
Keywords: Gambling; Gambling -- Economic aspects